2018
DOI: 10.3389/fphys.2018.01562
|View full text |Cite
|
Sign up to set email alerts
|

Acute Dehydration Impairs Endurance Without Modulating Neuromuscular Function

Abstract: Introduction/Purpose: This study examined the influence of acute dehydration on neuromuscular function.Methods: On separate days, combat sports athletes experienced in acute dehydration practices (n = 14) completed a 3 h passive heating intervention (40°C, 63% relative humidity) to induce dehydration (DHY) or a thermoneutral euhydration control (25°C, 50% relative humidity: CON). In the ensuing 3 h ad libitum fluid and food intake was allowed, after which participants performed fatiguing exercise consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 46 publications
1
55
1
1
Order By: Relevance
“…Hypohydration impairs exercise through a range of mechanisms, including a reduction in blood plasma/volume, impaired cardiovascular function, muscle blood flow and thermoregulatory capacity [ 5 , 10 ]. Additionally, hypohydration has been hypothesised to influence neuromuscular function and psychological strain [ 11 ]. Given the far-reaching impacts of hydration on function and health, it is unsurprising that there is a large body of research evaluating hydration status in humans [ 2 , 4 , 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypohydration impairs exercise through a range of mechanisms, including a reduction in blood plasma/volume, impaired cardiovascular function, muscle blood flow and thermoregulatory capacity [ 5 , 10 ]. Additionally, hypohydration has been hypothesised to influence neuromuscular function and psychological strain [ 11 ]. Given the far-reaching impacts of hydration on function and health, it is unsurprising that there is a large body of research evaluating hydration status in humans [ 2 , 4 , 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several considerations when implementing urinary hydration assessments; i) a urine sample reflects all urine in the bladder since the previous void, thus the timing since the last void will influence results [ 26 ], ii) ingesting hypotonic fluids results in water being excreted before the intracellular and extracellular fluids equilibrate, this can result in erroneous urine results indicating euhydration [ 2 , 52 ], iii) when assessing acute dehydration and rehydration, urine variables poorly correlate to more robust measures such as P OSM due to hormonal changes during rehydration influencing the reabsorption of water and electrolytes [ 11 , 26 , 53 ], iv) previous research investigating the accuracy of urinary assessments is mixed, with research reporting it to be robust [ 30 , 52 , 54 ] while other research indicates the opposite [ 15 , 55 – 58 ], v) as with P OSM, there is a biological variation between individuals and hence, use of single cut-off points as opposed to comparisons with baseline measures is likely to produce erroneous results [ 5 , 28 ], vi) previous research has suggested the use of single spot measures be excluded entirely due to the large degree of potential confounding factors and questionable normative values [ 59 ], vii) the urinary excretion rate has identified as a potential confounder of concentration-based assessments which should be accounted for where possible, and, viii) urinary measures represent the renal response to fluid homeostasis and not real-time hydration status at a cellular level [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the consequences of dehydration on physical and mental levels, highlighting humoral changes and cognitive deficits, which not only compromise normal daily activities but can negatively affect sports performance [4][5][6]. More specifically, it has been shown that the inadequate restoration of fluids during exercise compromises neuromuscular function, increases fatigue perception, reduces technical skills, affecting metabolic and autonomic nervous system parameters [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of maintaining a euhydrated state, studies have shown individuals are not adequately replacing fluid during exercise [21]. Although many studies have investigated the physiological responses to dehydration [4][5][6][7][8][9][10][11][12], to our knowledge, no research has evaluated the impact of dehydration on both metabolic and neuromuscular variables during performance in active males. Therefore, the purpose of our study was to investigate the effects of progressive dehydration on heart rate (HR), oxygen uptake (VO 2 ), energetic cost, and neuromuscular functionality during both submaximal cycling exercise at a constant work rate and subsequent time-to-trial (TT) performance.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that insufficient hydration of the body, during and after exercise, determine the incapacity of maintaining the optimum parameters of the in cardiovascular and urinary capacity and thus lower athletic performance [22][23][24][25][26][27].…”
mentioning
confidence: 99%